Zikreyâtü meşâhîri ricâli’l-Magrib - 880-01 Kennûn, 1908-1989. (Tıtvân, Fas)
< 7> kitap (7. kitap 41 sayfa ; 8. kitap 46 sayfa ; 9. kitap 37 sayfa ; 10. kitap 30 sayfa ; 11. kitap 36 sayfa ; 12. kitap 33 sayfa ; 19. kitap 33 sayfa)